The Effect of Directors’ Educational Background and Return on Assets on Carbon Emission Disclosure: Evidence from Non-Financial Companies in Indonesia - Nursulistyo, Emy Dwi; Subangkit, Andreas; Anekawati, Fitri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Carbon emission disclosure has become a global issue as part of business sustainability practices. This study aims to examine the effect of directors’ educational background on carbon emission disclosure in non-financial industries in Indonesia. Educational background is reflected in board diversity, particularly directors with financial education such as economics, management, and accounting. This research employs a quantitative approach using secondary data derived from annual reports and/or sustainability reports of non-financial companies in Indonesia from 2019 to 2025. The population consists of all companies listed on the Indonesia Stock Exchange during the period. The sample includes 72 non-financial companies from sectors such as basic materials, consumer non-cyclical, consumer cyclical, energy, industrials, infrastructure, property and real estate, as well as transportation and logistics, selected using purposive sampling. The results indicate that directors’ educational background has a positive effect on carbon emission disclosure, as shown by a significance value of 0.0009 (< 0.05). Meanwhile, return on assets (ROA) has no significant effect on carbon emission disclosure, with a significance value of 0.9346 (> 0.05). These findings suggest that non-financial factors, particularly the educational background of directors, play a more important role in encouraging environmental disclosure. The study is expected to provide insights for companies in making strategic decisions, especially in considering the representation of directors with financial educational backgrounds as part of their commitment to business sustainability.